Handbook of Life Course Health Development 2017
DOI: 10.1007/978-3-319-47143-3_19
|View full text |Cite
|
Sign up to set email alerts
|

How Socioeconomic Disadvantages Get Under the Skin and into the Brain to Influence Health Development Across the Lifespan

Abstract: Socioeconomic disadvantage (SED) has adverse impacts on physical (Adler and Rehkopf 2008; Blair and Raver 2012; Braverman and Egerter 2008; Cohen et al. 2010; Poulton et al. 2002) and psychological (Adler and Rehkopf 2008; Bradley and Corwyn 2002; Grant et al. 2003) health development. SED is similar to low socioeconomic status (SES) which is based on occupation, income, and education or a composite of more than one of these indicators (McLoyd 1998). However, we conceptualize SED more broadly than socioeconomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 330 publications
(328 reference statements)
3
55
1
2
Order By: Relevance
“…Probably the most important take-home point of an evolutionary-developmental approach is that researchers should be more cautious in assuming that undesirable developmental outcomes reflect dysregulation of a biological system (e.g., see Kim et al 2017) and more open to the possibility that those outcomes may be part of adaptive-or formerly adaptive-strategies for survival and reproduction. As I have argued in detail elsewhere (Del Giudice 2014b, c), a life history framework is especially useful in teasing out the logic of potentially adaptive combinations of traits, highlighting critical factors in the environment, and bridging behavioral development with physical growth trajectories.…”
Section: Implications For Health Developmentmentioning
confidence: 99%
“…Probably the most important take-home point of an evolutionary-developmental approach is that researchers should be more cautious in assuming that undesirable developmental outcomes reflect dysregulation of a biological system (e.g., see Kim et al 2017) and more open to the possibility that those outcomes may be part of adaptive-or formerly adaptive-strategies for survival and reproduction. As I have argued in detail elsewhere (Del Giudice 2014b, c), a life history framework is especially useful in teasing out the logic of potentially adaptive combinations of traits, highlighting critical factors in the environment, and bridging behavioral development with physical growth trajectories.…”
Section: Implications For Health Developmentmentioning
confidence: 99%
“…During the early postpartum period, both structural and functional adaptation in the brain play an important role in parenting among new mothers (Kim, in press; Kim, Strathearn, & Swain, 2016b; Lonstein, Lévy, & Fleming, 2015). Among neural changes associated with parenting, researchers have identified that heightened amygdala sensitivity to infant emotional expressions, particularly positive expressions, play an important role in secure mother-infant attachment and sensitive parenting (Atzil, Hendler, & Feldman, 2011; Barrett & Fleming, 2011; Feldman, 2015; Swain et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Increased levels of stress have been suggested as one of the key pathways by which socioeconomic disadvantage is associated with elevated neural and behavioral reactivity to negative emotion (Hackman, Farah, & Meaney, 2010; Kim, Evans, Chen, Miller, & Seeman, in press; McEwen & Gianaros, 2010). Low-income mothers report higher levels of psychological distress during the postpartum period (Goyal, Gay, & Lee, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The chapter in this volume by Kim and colleagues (Kim et al 2017) highlights how new insights into multilevel influences on health development pave the way for a range of different interventions that will further clarify these relationships. New research on pregnancy and the first years of a child's life indicate not only that this is a sensitive period for child neurological development but that it is a period when a parent's brain may demonstrate higher levels of plasticity and undergo changes to support the parental role (Kim et al 2016).…”
Section: Intervention Researchmentioning
confidence: 99%
“…Given that parental brains are being remodeled at the same time that children's brains are developing, there are several potential ways to intervene so that parents modify home environments in developmentally optimizing ways for both their children and for themselves. Many potential interventions that span from cells to society have been studied in isolation, ranging from those that attempt to modify socioeconomic position via cash transfers to those that focus on harmonizing parenting approaches via co-parenting skills training (see Kim et al 2017;Duncan et al 2011;Feinberg et al 2009). Less research has been done to better understand how best to combine interventions into a more integrated, sustained, and sustainable developmentally optimizing strategy.…”
Section: Intervention Researchmentioning
confidence: 99%